2019
DOI: 10.3390/ijerph16132414
|View full text |Cite
|
Sign up to set email alerts
|

Moral Disengagement as an Explanatory Factor of the Polyivictimization of Bullying and Cyberbullying

Abstract: Background: The present study’s objectives were to: (1) Identify and analyze the prevalence of poly-victims, and (2) determine how the levels of moral disengagement and the various defence mechanisms that victims use to explain abusive behavior might function as predictors of poly-bullying. Methods: The sample consisted of 1328 participants of from 9 to 14 years old. The instruments used were two questionnaires. One allows the prevalence of bullying and cyberbullying victims to be identified and analyzed. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 54 publications
0
15
1
Order By: Relevance
“…In this sense, it has been empirically confirmed that, on many occasions, the new technologies are not used safely, which has favoured the appearance of unfavourable behaviour [ 4 ], among which cyberbullying stands out [ 5 ]. Cyberbullying constitutes a growing scientific interest [ 6 ], mainly due to the generalisation of this phenomenon among the youngest population in a massive way [ 7 ] being usually accompanied by the existence of bullying [ 8 , 9 ]. For this reason, cyberbullying is a social concern, which is present in all educational institutions [ 10 ] and, therefore, increasing knowledge about this new form of harassment seems to be fundamental in order to establish adequate and specific prevention strategies for each context.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, it has been empirically confirmed that, on many occasions, the new technologies are not used safely, which has favoured the appearance of unfavourable behaviour [ 4 ], among which cyberbullying stands out [ 5 ]. Cyberbullying constitutes a growing scientific interest [ 6 ], mainly due to the generalisation of this phenomenon among the youngest population in a massive way [ 7 ] being usually accompanied by the existence of bullying [ 8 , 9 ]. For this reason, cyberbullying is a social concern, which is present in all educational institutions [ 10 ] and, therefore, increasing knowledge about this new form of harassment seems to be fundamental in order to establish adequate and specific prevention strategies for each context.…”
Section: Introductionmentioning
confidence: 99%
“…It indirectly causes at least 200 deaths every year [2]. Though social awareness is growing, recent years have seen a greater number of cases diagnosed [3].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, some authors suggest that cyberbullying has more negative and adverse consequences for the victim than traditional bullying [27,28]. Of course, these detrimental effects are much more traumatic for the adolescent when he or she is subjected to a situation of poly-bullying victimization [29,30], which involves being a victim of both traditional bullying and cyberbullying [31][32][33] In fact, many authors show that there is a considerable overlap between traditional bullying and cyberbullying [4,24,25,34,35].…”
Section: Cyberbullying In the "Always On" Smartphone Generationmentioning
confidence: 99%